Gender-specific association of metabolic syndrome and its components with arterial stiffness in the general Chinese population - Yue, Mengjia (PLoS One, 2017)
OBJECTIVES: Metabolic syndrome (MS) is considered to be a cluster of interrelated risk factors for metabolism, which may increase arterial stiffness and cardiovascular morbidity. The cardio-ankle vascular index (CAVI) is a reliable indicator of arterial stiffness and early arteriosclerosis. The main objective of this study is to evaluate the gender-specific relationship between MS and CAVI in the general Chinese population. METHODS: A total of 1,301 subjects aged 20 to 60 years participated in this study. CAVI was measured noninvasively using a Vasera VS-1000 device. Blood samples and waist circumference were examined to identify metabolic syndrome according to the criteria set forth in the 2009 Joint Scientific Statement. RESULTS: The prevalence of MS in the study subjects was 17.4% (30.7% in males and 7.0% in females, P < 0.001). CAVI values were significantly higher in MS subjects than in non-MS subjects and increased linearly as the number of MS components increased in females, but not in males. Using multiple regression analysis, we found that BMI was correlated with CAVI in the overall population and in both genders, and that high-density lipoprotein cholesterol (HDL-C) was associated with CAVI in males, while the number of MS components was related to CAVI in females. CAVI values increased linearly with age in both genders (P-trend < 0.001 for both), and this correlation was stronger in males than in females. CONCLUSIONS: There are gender-specific differences in the association of MS and CAVI. First, the effects of the number of MS components on CAVI are stronger in females than in males. Second, the effect of each MS component on arterial stiffness may differ in relation to gender. In addition, aging affects arterial stiffness more severely in males, and the increase in arterial stiffness tends to occur at a younger age in males than in females. Larger samples and longitudinal studies are needed to further confirm our results in the future.